2019
DOI: 10.1039/c9nr02350j
|View full text |Cite
|
Sign up to set email alerts
|

Autoregenerative redox nanoparticles as an antioxidant and glycation inhibitor for palliation of diabetic cataracts

Abstract: The autoregenerative redox PEG-PLGA coating CeO2 nanoparticles can effectively protect lens epithelial cells from oxidative stress and restrain α-crystallin glycation and crosslinking, thereby alleviating diabetic cataracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…It has been reported that the size and concentration of the gold nanoparticles allowed variations in the total surface area of the colloidal suspensions influencing the extent modification of bovine serum albumin (BSA) with d-ribose [17], while selenium nanoparticles protected structural modifications of proteins during glycation [18]. Similarly, cerium dioxide nanoparticles were able to protect the lens epithelial cells from the damage of oxidative stress by scavenging reactive oxygen species (ROS) and further attenuate α-crystallin glycation by possessing antioxidant and antiglycation properties [19]. In addition, the previous study on ZnO-NPs synthesized from aqueous extract of Aloe vera leaf was found to be a potent antiglycation agent, as they could inhibit the formation of AGEs and protect the protein structure from modification [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the size and concentration of the gold nanoparticles allowed variations in the total surface area of the colloidal suspensions influencing the extent modification of bovine serum albumin (BSA) with d-ribose [17], while selenium nanoparticles protected structural modifications of proteins during glycation [18]. Similarly, cerium dioxide nanoparticles were able to protect the lens epithelial cells from the damage of oxidative stress by scavenging reactive oxygen species (ROS) and further attenuate α-crystallin glycation by possessing antioxidant and antiglycation properties [19]. In addition, the previous study on ZnO-NPs synthesized from aqueous extract of Aloe vera leaf was found to be a potent antiglycation agent, as they could inhibit the formation of AGEs and protect the protein structure from modification [16].…”
Section: Introductionmentioning
confidence: 99%
“…Bodoki et al, by comparison free lutein or lutein-loaded NPs administered orally or topically in selenite cataract, demonstrated that the severity of lens injury was significantly reduced in rats treated with topical applications of lutein-loaded NPs [22]. Recently, it was demonstrated that in diabetic cataract, autoregenerative redox nanoparticles can act as an antioxidant and glycation inhibitor [23].…”
Section: Resultsmentioning
confidence: 99%
“…[ 172,173 ] However, this review did not find any literature on nanomaterial‐mediated treatments for radiation‐induced ophthalmic diseases. Nevertheless, studies on eye oxidative disease therapy, using nanomaterials through the ROS‐scavenging approach, are readily available [ 174–176 ] and provide good guidance for radiation‐induced eye disease treatments because excess ROS generation is the main cause of eye damage under radiation exposure. For instance, Zheng et al.…”
Section: Discussionmentioning
confidence: 99%